2009
DOI: 10.1016/j.bbrc.2009.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Mouse sperm K+ currents stimulated by pH and cAMP possibly coded by Slo3 channels

Abstract: Slo3 channels belong to the high conductance Slo K + channel family. They are activated by voltage and intracellular alkalinization, and have a K + /Na + permeability ratio (P K /P Na ) of only approximately 5. Slo3 channels have only been found in mammalian sperm. Here we show that Slo3 channels expressed in Xenopus oocytes are also stimulated by elevated cAMP levels through PKA dependent phosphorylation. Capacitation, a maturational process required by mammalian sperm to enable them to fertilize eggs, involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 17 publications
6
66
0
Order By: Relevance
“…When expressed in Xenopus oocytes, SLO3 is also stimulated by elevated cAMP levels through a PKA-dependent phosphorylation. Patch-clamp recordings in testicular mouse spermatozoa revealed that a K ϩ current that is time and voltage dependent is activated by intracellular alkalinization, has a P K /P Na Ն5, is weakly blocked by TEA, and is very sensitive to Ba 2ϩ (346). These currents are absent in testicular spermatozoa from Slo3 null mice, confirming their identity.…”
Section: F Capacitationmentioning
confidence: 78%
See 1 more Smart Citation
“…When expressed in Xenopus oocytes, SLO3 is also stimulated by elevated cAMP levels through a PKA-dependent phosphorylation. Patch-clamp recordings in testicular mouse spermatozoa revealed that a K ϩ current that is time and voltage dependent is activated by intracellular alkalinization, has a P K /P Na Ն5, is weakly blocked by TEA, and is very sensitive to Ba 2ϩ (346). These currents are absent in testicular spermatozoa from Slo3 null mice, confirming their identity.…”
Section: F Capacitationmentioning
confidence: 78%
“…329,433). Since then, several ion channels have been detected in testicular and epididymal mouse spermatozoa (137,346,381,431,450,566). Intriguingly, Ca V 3 currents such as those recorded in spermatogenic cells were detected in testicular but not in epididymal sperm (137,566).…”
Section: Ca V Channels In Spermatogenic Cells and Spermatozoamentioning
confidence: 99%
“…Sperm were harvested from the seminiferous tubules of adult CD1 mice as previously described (28) and whole-cell currents in patch-clamped sperm using established methods (53). We used testicular sperm to avoid prior exposure of cells to endogenous (epididymal) CRISP4.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of insect sperm via ionotropic Ors is reminiscent of capacitation of mammalian sperm, which has been linked to signaling pathways mediated by metabotropic ORs (23,26,27) as well as the activity of several ionotropic channels (58,59). These include calcium channels, most notably the sperm cation channels, CatSpers (60)(61)(62)(63), potassium channels such as Kcnu1 (64,65) as well as sodium, proton, bicarbonate, and chloride channels that are localized along the sperm flagella and speculated to act downstream of receptors for diverse extracellular ligands (33,59). The modulation of insect and mammalian sperm via proteins of distinct evolutionary origins yet that encompass conserved modes of signal transduction represents a potent example of convergent evolution impacting upon a singularly essential biological process.…”
Section: Significancementioning
confidence: 99%